Pengaruh Penggunaan Storyboard sebagai Media Visual terhadap Kemampuan Menulis Teks Cerita Pendek di SMPN 4 Pancarijang - Anita Candra Dewi (FKIP UNSULTRA, 2025)
This study aims to determine the effect of using storyboards as visual media on the ability to write short story texts in SMPN 4 Pancarijang students. Storyboards are used to help students organize ideas systematically before they are poured into writing. The research method used is a quasi-experiment with a pretest-posttest control group design. The research sample consisted of 60 students of grade VIII who were divided into an experimental group and a control group. The instrument used was a short story text writing test. Data were analyzed using normality, homogeneity, and t-test tests. The results showed that there was a significant difference between the experimental group and the control group after treatment. The experimental group that used storyboards experienced a higher average writing score increase than the control group. These findings indicate that the use of storyboards is effective in improving students' ability to write short story texts. Storyboards help students develop storylines, organize characters, settings, and conflicts in a more structured manner. Based on these results, the use of visual media such as storyboards is highly recommended to be integrated into the writing learning process at the junior high school level. The implications of this study contribute to the innovation of Indonesian language learning media, especially in creative writing skills. Further research can explore the use of similar media for various other types of texts.